MSB analysis of a free flying helicopter with fully articulated rotor - Waitz, S. (My University, 2014)
Since Multi Body System (MBS) codes have been proved to be potentially powerful simulation tools in the whole range of helicopter rotor dynamics, here the question of modelling the free flying helicopter in a pure MBS as well as in a hybrid FEMBS dynamical simulation model is highlighted. The objectives of this research work are modelling techniques for describing the dynamical behaviour and the structural interaction between articulated helicopter rotors and the nacelle of a free flying helicopter. Here the focus lies on the coupling of the rotating structure of the fully elastic, hinged main rotor with the non-rotating parts of the body structure via a flexible rotor-nacelle interface. As simulation platform the 9 [to] generic model “Helicopter H9” has been used. Representing the research object for this investigation it serves as a demonstrator model and as dynamic reference configuration for both the MBS and the FEM calculations. For reasons of a better clarification of the rotor-fuselage coupling effects the center of gravity of the helicopter fuselage exhibits large offsets in all three coordinate directions. As a consequence we get a highly non-symmetrical dynamical system w.r.t. the main rotor axis and a rotated principal axes system. Concerning the specific dynamic coupling effects between rotor and nacelle a survey study with topics like the main rotor suspension (lateral and vertical) or the elasticity of the drive train had been conducted. In systematic variation of the respective stiffness values (over four decades) the results of different parameter studies are presented as numerical results for single constant rotor speeds as well as in frequency fan diagrams for the overall dynamical behaviour under the change of rotor speed. By applying different blade pitch and ?3 angles the influence of the blade pitch positon on the rotor eigenbehaviour has been tested. Even cases of stability loss of the free flying helicopter concerning elastic eigenmodes of the coupeled rotor-nacelle-system — an air resonance type — could be detected in this work. The validation of the models and the computational procedure had been done by comparing the eigenmodes and the eigenvalue results produced with the two elasto-mechanical methods MBS and FEM. Thus different algorithms and independent tools have been used in the examination. It has been shown that for the non-rotating as well as for the rotating test cases the coupling effects caused by the blade hinges and pitch angles will be reproduced without any restriction in both approaches. The FEMBS modification of the pure MBS model renders a hybrid formulation which can combine advantages of both sides. Thus the potential of a sophisticated MBS code like SIMPACK as a powerful simulation tool for helicopter dynamics of the free flying system has been demonstrated with respect to the characteristics of an articulated rotor.